Nuclear localization of a putative Phytophthora sojae bZIP1 transcription factor is mediated by multiple targeting motifs. Issue 4 (16th March 2017) - Fang, Yufeng; Tyler, Brett M.
Summary: Oomycetes are fungal‐like eukaryotic microbes in the kingdom Stramenopila. We recently found that the oomycete plant pathogen Phytophthora sojae uses nuclear localization signals (NLSs) for translocation of proteins into the nucleus that differ from conventional well‐characterized NLSs from mammals and yeast. Here, we have characterized in depth the NLSs of a P. sojae basic leucine zipper transcription factor, PsbZIP1. Nuclear localization of PsbZIP1 was determined by a central conserved region overlapping the DNA binding domain. Mutational analysis of this region identified four distinct elements that contributed multiplicatively to nuclear localization, but the conserved DNA binding residues were not required. Three of the elements showed autonomous NLS activity and the fourth served as a nuclear localization enhancer. Sequences within two of the nuclear localization elements defined a new form of bipartite NLS consisting of a triplet of basic residues followed by a tail of scattered basic amino acids. Abstract : Nuclear localization of the P. sojae bZIP transcription factor PsbZIP1 is determined by a central conserved domain consisting of 134 amino acids. At least three regions within this domain (NLS1, NLS2 and NLS3) show independent nuclear targeting activities. The three regions work together cooperatively along with a fourth enhancer region to produce efficient nuclear localization of PsbZIP1. NLS2 and NLS3 contain sequences that may define a new form of bipartite NLS.